Schefflera matsallehii - Damit, A.; Tsen, S.; Colin Ruzelion Maycock; Sugau, J.; Khoo, E.; Nilus, R.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Schefflera matsallehii was only recorded from a single locality in the lowland ultramafic forest of Bukit Tawai Forest Reserve, Sabah. This locality is located within a Totally Protected Area (TPA) and the most recent specimen collection was made in 2016. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2 and there is no decline. Forest fire is the major threat to the population of this species since its locality is close to settlements and farms. If this were to occur it could drive the species towards Critically Endangered or Extinct in the near future. Hence, it is assessed as Vulnerable. Schefflera matsallehii is endemic to Sabah, Malaysia. It is only known from a collection at Bukit Tawai Forest Reserve.